2012
DOI: 10.1186/1477-7525-10-74
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the osteoporosis quality of life questionnaire QUALEFFO-41 for the Serbian population

Abstract: BackgroundVertebral fractures could lead to reduced physical, social and mental functioning, and loss of personal independence. Therefore, during the treatment of osteoporosis, it has become necessary to examine the changes in everyday functioning, well-being and health related quality of life (HRQOL). To that effect, this study aims to translate, culturally adapt, and validate the Serbian version of Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO-41) for patients with verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
(38 reference statements)
1
20
0
3
Order By: Relevance
“…Sixteen studies that met all inclusion criteria were included in the final analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with a total of 3131 men and women (1698 with vertebral fracture, and 1433 without vertebral fracture). Fourteen of these studies were cross-sectional [13-17, 19, 20, 22-28], one case-control [21], and one baseline data from an RCT [18].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen studies that met all inclusion criteria were included in the final analysis [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with a total of 3131 men and women (1698 with vertebral fracture, and 1433 without vertebral fracture). Fourteen of these studies were cross-sectional [13-17, 19, 20, 22-28], one case-control [21], and one baseline data from an RCT [18].…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
“…Fourteen of these studies were cross-sectional [13-17, 19, 20, 22-28], one case-control [21], and one baseline data from an RCT [18]. The characteristics of the included studies are shown in Table 1.…”
Section: Description Of Studies Identifiedmentioning
confidence: 99%
See 3 more Smart Citations